2020
DOI: 10.9778/cmajo.20200148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on computed tomography usage and critical test results in the emergency department: an observational study

Abstract: (COVID-19) has had a major impact on the delivery of health care worldwide. 1 To prepare for a potential surge of patients with COVID-19 and to reduce the risk of COVID-19 transmission, many medical societies recommended that nonurgent medical procedures such as colonoscopy, Papanicolaou smears and mammography for cancer screening be delayed or rescheduled. 2-4 Preliminary data suggest that the volume of nonurgent procedures markedly decreased during the initial phase of the COVID-19 pandemic in North America.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
4
14
0
Order By: Relevance
“…As such, it is actually possible that we have underestimated the true rate of trauma as we only captured trauma patients who received a CT scan. Other studies have shown similar results with a higher proportion of presenting injuries requiring acute care with more severe injuries [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 66%
“…As such, it is actually possible that we have underestimated the true rate of trauma as we only captured trauma patients who received a CT scan. Other studies have shown similar results with a higher proportion of presenting injuries requiring acute care with more severe injuries [ 13 , 14 ].…”
Section: Discussionsupporting
confidence: 66%
“…During the pandemic, the number of imaging investigations performed has been increasing dramatically and it will continue to grow due to the persistent symptomatology in Long-COVID patients [47] . AI has numerous potential applications in diagnostic imaging, including image analysis, decision-making, and prognosis prediction [48] ( Figure 6 ) , and has been widely used in the fight against the COVID-19 pandemic [49] , [50] , [51] , [52] .…”
Section: Role Of the Aimentioning
confidence: 99%
“…With the background of CT utilization increasing, several studies have evaluated patterns of CT use during the COVID pandemic, finding a decline in the absolute number of CT orders [ 10 , 15 , 28 31 ]. These decreases have been attributed to decreased imaging of lower acuity patients [ 10 ]; however, the data are difficult to interpret given that EDs nationwide experienced a nearly 40% reduction in visit volumes during the early COVID pandemic [ 7 , 32 ].…”
Section: Introductionmentioning
confidence: 99%